Resting state functional connectivity in alcohol users and co-users of other substances. (April 2022) - Morris, Vanessa; Syan, Sabrina K; MacKillop, James; Amlung, Michael
Highlights: This study examined resting state functional connectivity (rs-FC) in participants who report using multiple or single substances. 82 adult participants were classified as mono, dual or tri+ substance users based on their reported use of alcohol, tobacco, cannabis, and illicit drugs. Three clusters differed significantly between the three groups, including occipital cortex in the temporal network and bilateral orbitofrontal cortex in the salience network. Tri+ users exhibited lowest functional connectivity in these regions. Findings indicate that use of three or more substances may significantly impact rs-FC within the salience and temporal networks. Abstract: Polysubstance use (PSU) is the use of more than one psychoactive substance simultaneously or independently, and occurs in roughly half of individuals who seek treatment for substance use. The current study sought to use resting state functional connectivity (rs-FC) to examine functional connectivity in participants who report using multiple or single substances. Participants were drawn from a larger neuroimaging study. From there, participants were placed into one of three groups based on their frequency of alcohol, tobacco, cannabis, and illicit drug use. The final sample consisted of 82 participants. We observed three clusters that differed significantly between the three groups; one within the salience network and two within the temporal network. Tri+ users were found to have a lesser amount of rs-FC in these regions (compared to the other two groups) and dual users were found to have a greater amount of rs-FC within these regions. Findings indicate that use of three or more substances may significantly impact rs-FC within the salience and temporal networks, and that those who use alcohol+cannabis have significantly greater rs-FC than those who use alcohol+tobacco. Research is needed to examine larger samples of PSU for comparisons across specific substance combinations.